2001
DOI: 10.1054/bjoc.2001.1881
|View full text |Cite
|
Sign up to set email alerts
|

Growing vascular endothelial cells express somatostatin subtype 2 receptors

Abstract: SummaryWe hypothesized that non-proliferating (quiescent) human vascular endothelial cells would not express somatostatin receptor subtype 2 (sst 2) and that this receptor would be expressed when the endothelial cells begin to grow. To test this hypothesis, placental veins were harvested from 6 human placentas and 2 mm vein disks were cultured in 0.3% fibrin gels. Morphometric analysis confirmed that 50-75% of cultured vein disks developed radial capillary growth within 15 days. Sst 2 gene expression was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 21 publications
2
47
1
2
Order By: Relevance
“…Previous studies have demonstrated the expression of SSTR2A and SSTR5 in fibrovascular stroma of nontumoral tissues (endothelial and immune cells) [39]; however, the expression of SSTR3 is a relative novel finding. This pattern is mainly encountered in endothelial cells of rapidly proliferating vessels and it might be correlated to neoangiogenesis [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the expression of SSTR2A and SSTR5 in fibrovascular stroma of nontumoral tissues (endothelial and immune cells) [39]; however, the expression of SSTR3 is a relative novel finding. This pattern is mainly encountered in endothelial cells of rapidly proliferating vessels and it might be correlated to neoangiogenesis [40]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, another mechanism by which SST and its analogs may exert their antiproliferative effects is the inhibition of tumor neoangiogenesis. Growing vascular endothelial cells express several SSTR subtypes (1,62), and SST regulation of tumor angiogenesis has been described in human glioma cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that support the potential anti-angiogenic effect of S Grozinsky-Glasberg et al: Somatostatin action in NETs www.endocrinology-journals.org SST and its analogues. One study hypothesised that non-proliferating human vascular endothelial cells do not express SSTR 2 but that this receptor is expressed when the endothelial cells begin to grow (Watson et al 2001); the SSTR 2 gene was expressed, and the presence of SSTR 2 on proliferating angiogenic vessels was confirmed, by immunohistochemical staining and in vivo scintigraphy, suggesting that SSTR 2 may be a specific target for anti-angiogenic therapy with SSTR 2 -binding SSAs conjugated to radioisotopes or cytotoxic agents.…”
Section: Sst's Effect On Tumour Angiogenesismentioning
confidence: 99%